KETERPENGARUHAN UMAT ISLAM TERHADAP SUKU BUNGA: STUDIEMPIRIS PERMINTAAN UANG INDONESIA 1983-2000 - Santosa, Purbayu Budi; Widodo, N.; Riyardi, Agung (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2004)
Normatively, moslems economic behaviors do not rely on interest rate. Unfortunately, economic system encompassing them based on interest rate. More over monetary authority determines interest rate as a means to control economy via deregulasi sektor moneter. In that contradictive situation, it is to ask whether moslems hold on to their religion or not. We estimate a relationship between interest rate and demand for money, but there was moslems hesistancy.Utilizing ECM, with demand for uang primer riil as dependent variable and suku bunga deposito 3 bulan, suku bunga LIBOR, GDP riil, and kurs US dollar terhadap rupiah as independent variables from 1983 until 2000, we found that there was a nonsignificant shortterm relationship between interest rate and demand for money. But there was a significant longterm relationship between interest rate and demand for money. It is to conclude that moslems did not use interest rate as an instrument to hold money. They held on to their religion, riba prohibition, like Al-Baqarah verses 278-279 said. But Moslems still used interest rate as an instrument to increase riel sector activity, i.e. to increase economic growth.